2021
DOI: 10.3390/ijms22031062
|View full text |Cite
|
Sign up to set email alerts
|

Pathomechanism Characterization and Potential Therapeutics Identification for Parkinson’s Disease Targeting Neuroinflammation

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disorder characterized by the loss of dopaminergic (DAergic) neurons and the presence of α-synuclein-containing Lewy bodies. The unstructured α-synuclein forms insoluble fibrils and aggregates that result in increased reactive oxygen species (ROS) and cellular toxicity in PD. Neuroinflammation engaged by microglia actively contributes to the pathogenesis of PD. In this study, we showed that VB-037 (a quinoline compound), glycyrrhetic acid (a pentacyclic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 74 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Previous evidence also proposed that persistent neuroinflammation is linked to PD pathophysiology. 30 It is presumed that higher activated microglial levels of proinflammatory mediators impair neurons. This may lead to neuroinflammation and neurodegeneration in PD.…”
Section: Resultsmentioning
confidence: 99%
“…Previous evidence also proposed that persistent neuroinflammation is linked to PD pathophysiology. 30 It is presumed that higher activated microglial levels of proinflammatory mediators impair neurons. This may lead to neuroinflammation and neurodegeneration in PD.…”
Section: Resultsmentioning
confidence: 99%
“…BV-2 cells are often used to investigate neuroinflammation affected by activated microglia [ 36 , 37 , 38 ]. Studies have shown that IFN-γ can induce BV-2 cell activation, which causes NO production [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…High glucose-induced extracellular matrix accumulation↓, oxidative stress↓, IL-6 and IL-1β production↓, NF-κB and NLRP3 inflammasome pathways↓ [47] Echinatin Mouse BMDMs and human PBMCs Bind to heat-shock protein 90↑, ATPase activity↓, the association between the cochaperone SGT1 and HSP90-NLRP3↓ [50] LPS-induced septic shock mouse model IL-1β↓, TNF-α production↓, mouse survival↑ [50] Dextran sodium sulfate-induced colitis mouse model Colonic inflammation↓, mucosal barrier and inflammatory cell infiltration↓, caspase-1 activation↓, IL-1β production↓ [50] MCD diet-induced NASH mouse model Morphological changes↓, hepatic steatosis↓, ballooning↓, fibrosis↓, caspase-1 activation↓, mRNA expression of proinflammatory genes IL-1β and TNF-α↓ [50] (Continued) Carrageenan-induced pleurisy mouse model TNF-α↓, IL-1β↓, IL-6↓, the NLRP3/NF-κB pathway↓, iNOS↓, COX-2↓ [68] The mouse periodontal ligament fibroblasts Chronic periodontitis↓, caspase-1 activation↓, IL-1β↓, HMGB1↓, ROS/ TXNIP/Nlrp3 inflammasome pathway↓ [67] Collagenase IV-induced intracerebral hemorrhage rat model Neurological deficits↓, histological damages↓, blood-brain barrier disruption↓, brain edema↓, neuronal degeneration↓, the NF-κB and NLRP3 inflammasome pathways↓, Nrf2-mediated antioxidant system↑ [58] LPS-induced ALI mouse model Recruitment of inflammatory cells↓, COX-2↓, iNOS↓, TNF-α↓, IL-1β↓, IL-6↓, the AMPK/Nrf2 signaling and its downstream antioxidant enzymes↑, the NLRP3 inflammasome and NF-κB pathways↓ [62] In vitro model of ischemia in organotypic slice cultures Ischemic neuronal death↓, NLRP3 inflammasome activation↓ [55] Indomethacin-induced small intestinal damage mouse model Small intestinal damage↓, cleaved caspase-1↓, mature IL-1β protein levels↓ [63] Ex vivo culture of epididymal white A corneal injury mouse model The expression of IL-1β↓, extracellular HMGB1 functions↓, the NF-κB-p65/ NLRP3/IL-1β signaling pathway↓ [89] An acute glaucoma mouse model The severity of the disease↓, the activation of NLRP3 and caspase-8 inflammasomes↓ [92] Traumatic spinal cord injury rat model Expression of NLRP3 inflammasome components↓, ASC↓, NLRP3↓, cleaved caspase-1↓, IL-1β↓, IL-18↓ [95] GA Mouse BV-2 microglial cells Nitric oxide↓, IL-1β maturation↓ [102] LPS-induced ALI mouse model ALI↓, the activation of NLRP3 inflammasome↓, ROS-PI3K/AKT pathway↓ [96] (Continued) Carbenoxolone HFD-induced obese mouse model Insulin sensitivity↓, the IκB-α/NF-κB pathway and NLRP3 inflammasome↓, [106] Licorice extract Irinotecan-induced colitis mouse model The mRNA and protein levels of TNF-α↓, IL-1β↓, and IL-6↓ [107] Notes: ↓, inhibition; ↑, promotion.…”
Section: Dovepressmentioning
confidence: 99%
“…97,98 A large amount of evidence confirms the relationship between Parkinson's and NLRP3 inflammasome. [99][100][101] GA, Glycyrrhiza inflata, and Shaoyao Gancao decoction (a formulated Chinese medicine) all exhibit anti-inflammatory effects that ameliorate neurotoxicity induced by α-synuclein in BV-2 and A53T SNCA-GFP SH-SY5Y cells by suppressing NLRP1/ NLRP3 inflammasome, IL-1β-mediated IκBα/P65, JNK/ JUN, P38/STAT1, and IL-6-mediated JAK2/STAT3 pathways; 102 This indicates that related components and preparations of licorice may be used as drugs for the treatment of neurodegenerative diseases such as PD.…”
mentioning
confidence: 99%